Perancangan Sistem Informasi Jurnal Perkuliahan Sebagai Upaya Monitoring dan Evaluasi Proses Pembelajaran (Studi Kasus : Prodi Teknik Industri Fakultas Teknik Universitas Kadiri) - Imam Safi'i (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2017)
In the learning process at the Industrial Engineering Study Program, Faculty of Engineering, Kadiri University, monitoring is carried out by looking at the results of the lecture journal entry, which is one of the lecture administration sections. Lecture journal documents contain material delivered by the lecturer to students at each lecture meeting aimed at information and data on the lecturing process. This research aims to design an information system monitoring and evaluation of the learning process through lecture journals in the S-1 Department of Industrial Engineering, Faculty of Engineering, University of  Kadiri which is expected to be able to provide solutions in monitoring and evaluation of learning activities that are transparent, accountable and real-time. The study begins by analyzing system requirements, then modeling with UML by making usecase diagrams, class diagrams and activity diagrams. The system design uses the help of CMS Wordpress and Google Form applications. This research resulted in a monioring information system design and learning process evaluation at the Industrial Engineering Study Program at the Kadiri University Faculty of Engineering in the form of online lecture journal filling services and data stored safely in the cloud. So that monitoring and evaluation activities can be more effective and efficient.Dalam proses pembelajaran di Program Studi Teknik Industri Fakultas Teknik Universitas Kadiri, monitoring dilakukan dengan melihat hasil pengisian jurnal perkuliahan, yaitu salah satu bagian administrasi perkuliahan. Dokumen jurnal perkuliahan berisi mengenai materi yang disampaikan Dosen kepada mahasiswa pada setiap pertemuan kuliah yang bertujuan untuk informasi dan data proses perkuliahan berlangsung. penelitian ini bertujuan merancang sebuah sistem informasi monitoring dan evaluasi proses pembelajaran melalui jurnal perkuliahan di Prodi S-1 Teknik Industri Fakultas Teknik Universitas Kadiri yang dimana diharapkan mampu memberi solusi dalam kegiatan monitoring dan evaluasi pembelajaran yang transparan, akuntabel dan realtime. Penelitian diawali dengan menganalisis kebutuhan sistem, kemudian melakukan pemodelan dengan UML dengan membuat usecase diagram, class diagram dan activity diagram. Perancangan sistem menggunakan bantuan aplikasi CMS Wordpress dan Google Form. Penelitian ini menghasilkan sebah rancang bangun sistem informasi monioring dan evaluasi proses pembelajaran pada Prodi Teknik Industri Fakultas Teknik Universitas Kadiri berupa layanan pengisian jurnal perkuliahan secara online dan data tersimpan aman di cloud. Sehingga kegiatan monitoring dan evaluasi bisa lebih efektif dn efisien.